A Dominant Mutation in the Light-Oxygen and Voltage2 Domain Vicinity Impairs Phototropin1 Signaling in Tomato. Issue 4 (10th February 2014) - Sharma, Sulabha; Kharshiing, Eros; Srinivas, Ankanagari; Zikihara, Kazunori; Tokutomi, Satoru; Nagatani, Akira; Fukayama, Hiroshi; Bodanapu, Reddaiah; Behera, Rajendra K.; Sreelakshmi, Yellamaraju; Sharma, Rameshwar
Abstract : A single mutation abolishes phototropin1-specific responses, indicating that the helix region has an essential role in phototropin signaling . Abstract: In higher plants, blue light (BL ) phototropism is primarily controlled by the phototropins, which are also involved in stomatal movement and chloroplast relocation. These photoresponses are mediated by two phototropins, phot1 and phot2. Phot1 mediates responses with higher sensitivity than phot2, and phot2 specifically mediates chloroplast avoidance and dark positioning responses. Here, we report the isolation and characterization of a Nonphototropic seedling1 ( Nps1 ) mutant of tomato ( Solanum lycopersicum ). The mutant is impaired in low-fluence BL responses, including chloroplast accumulation and stomatal opening. Genetic analyses show that the mutant locus is dominant negative in nature. In dark-grown seedlings of the Nps1 mutant, phot1 protein accumulates at a highly reduced level relative to the wild type and lacks BL -induced autophosphorylation. The mutant harbors a single glycine-1484-to-alanine transition in the Hinge1 region of a phot1 homolog, resulting in an arginine-to-histidine substitution (R495H) in a highly conserved A′α helix proximal to the light-oxygen and voltage2 domain of the translated gene product. Significantly, the R495H substitution occurring in the Hinge1 region of PHOT1 abolishes its regulatory activity in Nps1 seedlings, thereby highlighting the functional significance of the A′α helix region in phototropic signaling of tomato.